Soil Study for Site Suitability Appraisal of Forest Plantations in North Bihar - Yadav, J. S. P. (Indian Forester, 1969)
A soil investigation was undertaken in January 1966 to evaluate the soil factors in relation to the good and poor growth of forest plantations in North Bihar and to judge site suitability for such plantations. The soil is riverain sand characterised by a relatively finer-textured top layer, the thickness of which is of paramount practical significance in this context. Soils of Champaran district are mostly calcareous, alkaline and show considerable textural variations, whereas those of Purnea district are non-calcareous, acidic and more sandy. In general, the soils with deep finer-textured top layer associated with greater moisture and nutrient availability support much better growth of the planted species like bamboo, teak, Eucalyptus hyhrid and sissoo than the soils which have thin finer-textured top layer over deep deposit of coarse sand. Differences in local water table caused by micro-relief as also soil morphological features are further important in conditioning the growth of the plantations. Sites subjected to prolonged water-logging in rains are not suitable for Eucalyptus hybrid. The rooting habit of the species needs to be correlated to the soil conditions and moisture regime of the locality for proper site selection. As a rule, shallow-rooted species like bamboo should be grown on the soils having deep finer-textured productive zone. Growing of Tephrosia improves organic matter status and moisture relations of the soil. On the whole, cashew is a complete failure, while sissoo appears to be the most hardy species in this area.